Cost Uncertainty and Time Overruns in Public Procurement: a Scoring Auction for a Contract with Delay Penalties - Cesare Dosi; Michele Moretto (Fondazione Eni Enrico Mattei (FEEM), 2017)
Drawing on the real-options theory we analyse bidding behaviour in a sealed-bid-first-score procurement auction where suppliers, facing variable production costs, must simultaneously report the contract price and the cost level at which they intend to perform the project. We show that this award mechanism is potentially able to maximize total welfare. Next we look at the time incentives required to ensure compliance with the promised optimal trigger value. We show that ex-post efficiency may call for delay penalties higher than the anticipated harm caused by time overruns, in so doing questioning the efficiency rationale of existing liquidated damages rules.
Keywords: C61; D44; D86; K12; 330; Public Procurement; Fixed-price Contracts; Real Options; Time Overruns; Scoring Auctions; Liquidated Damages